Enzymatic profile of Pseudomonas maltophilia. - O'Brien, M (J Clin Microbiol, 1982)
An enzymatic profile of 20 strains of Pseudomonas maltophilia was undertaken with conventional plate tests, API ZYM, and 4-methylumbelliferyl-conjugated substrates. All strains produced DNase, RNase, arbutinase, esterases and lipases, mucinase, acid and alkaline phosphatases, alkaline pyrophosphate diesterase, phosphoamidase, beta-glucosidase, leucine arylamidase, and acetatase and were hemolytic for horse, sheep, and rabbit blood. The majority of strains produced chitinase, hyaluronidase, albuminase, valine arylamidase, trypsin, alpha- and beta-glucosidases, and N-acetyl-beta-glucosaminidase. API ZYM and 4-methylumbelliferyl-conjugated substrate assays are rapid, simple, specific, and sensitive and may be useful as diagnostic aids in the identification of P. maltophilia and other pseudomonads.